Psychotherapy for Attention Deficit Hyperactivity Disorder (ADHD) in Children - Yongmei, Hou (Disease and Health Research: New Insights Vol. 3, 2024)
Background: Psychotherapy is commonly used to treat children with attention-deficit/hyperactivity disorder (ADHD) due to its minimal side effects and enduring therapeutic benefits. It can effectively improve the attention of children with ADHD, reduce negative emotions, enhance positive emotions, correct problematic behaviors, cultivate good behavioral habits, and promote the development of intelligence and adaptability. Objective: To explore the research progress of psychotherapy applied in the treatment of children with ADHD, and provide reference opinions for clinical medicine, family rearing, and school education. Methods: The literature search method is used to organize 76 domestic and international articles, analyze the commonly used psychotherapy for ADHD, explain their principles, effects, and shortcomings, and based on this, propose research prospects. Results: Psychotherapy can not only improve the emotional, cognitive, and social functions of children with ADHD but also alleviate the parenting pressure. It has no side effects and a low recurrence rate, but it has drawbacks such as requiring lengthy treatment periods and showing slow effectiveness. Conclusion: Psychotherapy is a research hotspot in the treatment of ADHD, with broad prospects. However, there is room for improvement in the formulation and implementation of treatment plans, as well as feedback on their effectiveness.